2010
DOI: 10.1007/s10597-010-9299-z
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Involvement, Behavioral Health Service Use, and Costs of Forensic Assertive Community Treatment: A Randomized Trial

Abstract: Jail diversion and forensic community treatment programs have proliferated over the past decade, far outpacing evidence regarding their efficacy. The current study reports findings from a randomized clinical trial conducted in California for frequent jail users with serious mental illness that compares a forensic assertive community treatment (FACT) intervention with treatment as usual (TAU). Outcomes are reported at 12 and 24 months post-randomization for criminal justice outcomes, behavioral health services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 23 publications
(19 reference statements)
0
81
0
2
Order By: Relevance
“…114 Case management-Four studies assessed the impact of case management on health care use, 56,78,112,142 2 of which had positive findings. 56, 78 A study of forensic assertive community treatment in persons with a major mental illness found that those who received assertive community treatment had more outpatient visits and fewer days of hospitalization over 2 years of follow-up compared with those who received treatment as usual, but there was no difference between groups in the rate of hospitalization. 78 In persons with severe mental illness, a Critical Time Intervention to identify and manage priority problems before release and to continue support after release did not affect mental health or alcohol or substance abuse service use, but did increase primary care access and medication adherence.…”
Section: Health Service Use Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…114 Case management-Four studies assessed the impact of case management on health care use, 56,78,112,142 2 of which had positive findings. 56, 78 A study of forensic assertive community treatment in persons with a major mental illness found that those who received assertive community treatment had more outpatient visits and fewer days of hospitalization over 2 years of follow-up compared with those who received treatment as usual, but there was no difference between groups in the rate of hospitalization. 78 In persons with severe mental illness, a Critical Time Intervention to identify and manage priority problems before release and to continue support after release did not affect mental health or alcohol or substance abuse service use, but did increase primary care access and medication adherence.…”
Section: Health Service Use Interventionsmentioning
confidence: 99%
“…56, 78 A study of forensic assertive community treatment in persons with a major mental illness found that those who received assertive community treatment had more outpatient visits and fewer days of hospitalization over 2 years of follow-up compared with those who received treatment as usual, but there was no difference between groups in the rate of hospitalization. 78 In persons with severe mental illness, a Critical Time Intervention to identify and manage priority problems before release and to continue support after release did not affect mental health or alcohol or substance abuse service use, but did increase primary care access and medication adherence. 56 In adults infected with HIV, intensive case management before and after release compared with usual care did not affect clinic follow-up, hospitalization, or emergency room or urgent care visits in the year after release.…”
Section: Health Service Use Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown an association between mental health treatment and reduced rates of arrest and recidivism [10][11][12][13][14][15][16][17][18]. However, many Americans with mental health conditions who are at a higher risk of arrest, due to low income for example, go untreated [19].…”
Section: Introductionmentioning
confidence: 99%